2015
DOI: 10.1371/journal.pone.0134111
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental Modulation of Decorin and Lumican in Temozolomide-Resistant Glioblastoma and Neuroblastoma Cancer Stem-Like Cells

Abstract: The presence of cancer stem cells (CSCs) or tumor-initiating cells can lead to cancer recurrence in a permissive cell–microenvironment interplay, promoting invasion in glioblastoma (GBM) and neuroblastoma (NB). Extracellular matrix (ECM) small leucine-rich proteoglycans (SLRPs) play multiple roles in tissue homeostasis by remodeling the extracellular matrix (ECM) components and modulating intracellular signaling pathways. Due to their pan-inhibitory properties against receptor tyrosine kinases (RTKs), SLRPs ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 81 publications
2
30
0
Order By: Relevance
“…4,5 Understanding which factors promote stemness and treatment resistance of glioma cells is of intense interest in developing new therapies in glioma. A large number of studies over the past decade have established that there is considerable plasticity in glioblastoma cell phenotypes, [6][7][8][9][10][11] that stem cell characteristics can be acquired by non-stem-like cells, 8,9,[12][13][14][15] and that microenvironmental cues such as hypoxia, 16 extracellular matrix proteins, [17][18][19][20][21][22][23][24][25] or growth factors secreted by stromal cells [26][27][28] may be sufficient to induce tumor cell stemness and therapeutic resistance. The role of the microenvironment in regulating tumor stemness is further supported by the finding that stem-like tumor cells are enriched in specific tumor niches; in GBM, primarily the perivascular niche (PVN) and hypoxic compartments.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Understanding which factors promote stemness and treatment resistance of glioma cells is of intense interest in developing new therapies in glioma. A large number of studies over the past decade have established that there is considerable plasticity in glioblastoma cell phenotypes, [6][7][8][9][10][11] that stem cell characteristics can be acquired by non-stem-like cells, 8,9,[12][13][14][15] and that microenvironmental cues such as hypoxia, 16 extracellular matrix proteins, [17][18][19][20][21][22][23][24][25] or growth factors secreted by stromal cells [26][27][28] may be sufficient to induce tumor cell stemness and therapeutic resistance. The role of the microenvironment in regulating tumor stemness is further supported by the finding that stem-like tumor cells are enriched in specific tumor niches; in GBM, primarily the perivascular niche (PVN) and hypoxic compartments.…”
Section: Introductionmentioning
confidence: 99%
“…In colon cancer, LUM triggers cytoskeletal remodeling and elevates the cellular migration capacity [21], and, in bladder cancer, LUM expression promotes cell proliferation and migration [22]. In glioblastoma and NB, LUM expression is associated with the maintenance of a quiescent, drug-resistant, stem-cell-like phenotype [23]. Here, we report for the first time that LUM is a FOXO3-regulated gene involved in the cellular migration of neuronal tumor cells.By screening the Prestwick Chemical Library ® , containing 1120 FDA-approved drugs, we recently identified and characterized carbenoxolone (CBX) as the first FOXO3 inhibitor that overcomes FOXO3-mediated chemoprotection in high-stage NB [24].…”
mentioning
confidence: 71%
“…In NB, high LUM expression is associated with lower overall survival ( Figure S2). Of note, Farace et al reported that LUM expression is associated with the maintenance of a quiescent, drug-resistant, stem-cell-like phenotype in NB and glioblastoma cells [23]. However, the impact of LUM on neuronal tumor cell migration has not been investigated to date.…”
Section: Discussionmentioning
confidence: 99%
“…Expressional deregulation of many other proteins are also causally linked to the dedifferentiation of nonstem cancer cells and formation of iCSCs [118,[145][146][147] . For instance, Lamin A/C, the type V intermediate filaments of nuclear lamina, is often reduced or absent in proliferative cells of various tumors [148,149] .…”
Section: Induced Cscs and Therapy Resistancementioning
confidence: 99%
“…Further, treatment with Ruxolitinib (JAK2/STAT3 inhibitor) or Trametinib (MEK/ERK1/2 inhibitor) significantly enhanced the response of NB tumors to etoposide [166] . The ECM small leucine-rich proteoglycans (SLRPs), including decorin (DCN) and lumican (LUM), exhibited acquired upmodulation during NB-CSC enrichment [146] . Further, these small leucine rich proteoglycans (SLRP)-positive NB-CSCs were highly resistant to temozolomide (TMZ), demonstrating that (1) CSCs promote huge quantities of DCN and LUM; and (2) increased SLRPs promote acquired TMZ resistance, cellular heterogeneity, and a quiescent phenotype.…”
Section: Role Of Tme In Influencing Csc Status and Therapy Resistancementioning
confidence: 99%